Management level of zakat fi sabilillah among ACIS student in UiTM Puncak Alam / Siti Syazliyani Yusri - Yusri, Siti Syazliyani (2019)
Financial problems today are often the issue of rising costs. These financial problems are also faced by students who are pursuing higher education. Most students today are often influenced by peers, the latest trends and more. Due to the financial problems that arise among students, many problems arise for example they are vulnerable to depression when exposed to financial problems. The aim of this research is to examine the factor that influence students to manage the zakat that they receive among Academy of Contemporary Islamic Studies (ACIS) in UiTM Puncak Alam. This research is based on data obtained from a survey questionnaire that have been distributed among ACIS students in UiTM Puncak Alam. The data was analyzed by Statistical Package for Social Science (SPSS) to identify the factors that influence students to manage the zakat that they receive. The result of the study show that students understand about the concept of zakat in Islam and most of students manage the aid wisely. Furthermore, students agree that zakat aid was mostly use to finance their studies such as study fee and so on. This is because the zakat aid is provided at the beginning of the semester where students are required to use it for the payment of tuition fees It is hoped that this study will help the charity center identify the needs of students in their studies.